1987
DOI: 10.5860/crl_48_06_513
|View full text |Cite
|
Sign up to set email alerts
|

Material Availability: A Study of Academic Library Performance

Abstract: This article reports the findings of a study modeled after Saracevic, Shaw, and Kantor's efforts to identify and quantify the causes of users' failures to identify and locate library materials. The researchers analyzed patron-reported and librarian-observed subject and known-item searchesThe primary purpose of the study was to determine what needed to be done to improve library services. Several important ancillary benefits were anticipated; these included involving staff, particularly those new to the organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Reports of research can be found in: Gore (1975), Kantor (1976), Saracevic (1977), Smith and Granade (1978), Whitlatch and Kieffer (1978), Rinkel and McCandless (1983), Kantor (1984), Mansbridge (1986), Ciliberti et al (1987, Jacobs and Young (1995), and McCarthy (1995). All of these studies relate to availablity of monographs in University libraries.…”
Section: Background: Previous Researchmentioning
confidence: 96%
“…Reports of research can be found in: Gore (1975), Kantor (1976), Saracevic (1977), Smith and Granade (1978), Whitlatch and Kieffer (1978), Rinkel and McCandless (1983), Kantor (1984), Mansbridge (1986), Ciliberti et al (1987, Jacobs and Young (1995), and McCarthy (1995). All of these studies relate to availablity of monographs in University libraries.…”
Section: Background: Previous Researchmentioning
confidence: 96%
“…He identified several areas where a user was likely to encounter an issue starting with an item not being acquired and progressing through other problem areas such as circulation and shelving, cataloging errors, and user errors. Ciliberti et al (1987) built upon Kantor's model and conducted a similar study at the William Paterson College Library in New Jersey to determine why users could not find material on the shelves. One interesting finding was that for known-item searches, "of the 206 patrons who had correct information, 21 (19 %) were searching for titles the library had not purchased."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Untidy shelves where books are in any but the prescribed order, large numbers of books still awaiting shelving, or books "shelved" on the floor in front of their bookcases, as a result, perhaps, of the ever-increasing flood of publications acquired but not managed by the library, effectively prevent users from finding what they could rightly expect to find on the strength of catalogue and loans records. Ciliberti et al [15] describe a survey conducted at William Paterson College of New Jersey Library, which indicated some reasons for student failure to retrieve materials. An evaluation of the research showed that 63 per cent of all search failures could be considered library errors, i.e.…”
Section: □ Librarians Still Often Leave Users To Their Own Devices □mentioning
confidence: 99%